2017
DOI: 10.2118/175101-pa
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Hydrocarbon Permeability After Hydraulic Fracturing: Laboratory Evaluations of Shut-Ins and Surfactant Additives

Abstract: Summary Fracturing-fluid loss into the formation can potentially damage hydrocarbon production in shale or other tight reservoirs. Well shut-ins are commonly used in the field to dissipate the lost water into the matrix near fracture faces. Borrowing from ideas in chemical enhanced oil recovery (CEOR), surfactants have potential to reduce the effect of fracturing-fluid loss on hydrocarbon permeability in the matrix. Unconventional tight reservoirs can differ significantly from one another, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 1 publication
0
31
2
Order By: Relevance
“…The corresponding matrix notation is f = kd (19) where and are the node force, N; k is the stiffness matrix of the spring element, N/m; d is the node displacement vector, m; f is the node force vector, N. During SLFTP, the previously created fractures were plugged by diverting agents; thus the injected fracturing fluid and proppants were not able to flow back to the wellbore and retained within fractures. Moreover, the fluid leak-off rate was low due to the low-permeability [36][37][38]; thus the fracturing fluid and proppants trapped in the fracture space will prevent the previous fractures from closure. The propped fractures would squeeze the surrounding rocks and alter local stress fields, which may affect the injection pressure of the subsequent fractures created in other layers.…”
Section: Spring Modelmentioning
confidence: 99%
“…The corresponding matrix notation is f = kd (19) where and are the node force, N; k is the stiffness matrix of the spring element, N/m; d is the node displacement vector, m; f is the node force vector, N. During SLFTP, the previously created fractures were plugged by diverting agents; thus the injected fracturing fluid and proppants were not able to flow back to the wellbore and retained within fractures. Moreover, the fluid leak-off rate was low due to the low-permeability [36][37][38]; thus the fracturing fluid and proppants trapped in the fracture space will prevent the previous fractures from closure. The propped fractures would squeeze the surrounding rocks and alter local stress fields, which may affect the injection pressure of the subsequent fractures created in other layers.…”
Section: Spring Modelmentioning
confidence: 99%
“…Although the above method can effectively improve the oil recovery of low‐permeability oil layers, there are still many deficiencies. For hydraulic fracturing technology, only a small part of the injected fracturing fluid can be recovered, and most of the injected fracturing fluid remains in the formation, 29,30 and the remaining fracturing fluid plugs the original connected pores and throats, resulting in a decrease in physical permeability 31 . In addition, the residual fracturing fluid may form two‐phase seepage resistance and reduce the effective permeability of the oil phase 32 ; for CO 2 flooding, CO 2 injection may bypass the remaining oil zone and tend to flow through fractures, resulting in low sweep efficiency 33‐35 ; for profile control, the injected gel permanently blocks the high‐permeability layer 36 .…”
Section: Introductionmentioning
confidence: 99%
“…In water-wet rocks, it is observed that the water block formed by the invaded fracture fluid predominantly exists at the matrix-fracture interface due to the capillary discontinuity between the high-permeable fracture and low-permeable matrix space surrounding it [4] [5]. Bertoncello et al (2014) [6], Liang et al (2015) [7], Odumabo et al (2014) [8] and Yan et al (2015) [9] have shown that with sufficient duration of shut-in period the water-block would imbibe away from the fracture face due to capillary redistribution resulting in improvement of relative permeability to hydrocarbon. But very long shut-in times could affect the operator adversely as the expenditures increase due to the high day-rate services offered by the service companies.…”
Section: Introductionmentioning
confidence: 99%